2020
DOI: 10.2147/ott.s244339
|View full text |Cite
|
Sign up to set email alerts
|

<p>5-HT<sub>7</sub> Receptor Contributes to Proliferation, Migration and Invasion in NSCLC Cells</p>

Abstract: Introduction: Because only a small portion of NSCLC (non-small-cell lung cancer) patients benefit from molecular targeted therapy or immunotherapy and do not develop therapeutic resistance, continued research on new targets is warranted. Serotonin has recently emerged as a growth factor for tumor cells, and its receptors may be potential therapeutic targets. The mechanism related to the behavior of the 5-HT 7 receptor in NSCLC remains unknown. Methods: Both gene expression analysis and immunohistochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Previous studies on pancreatic cancer cell lines and human tumor tissue microarray have shown the role of 5-HT 1B , 5-HT 1D , or 5-HT 2B in 5-HT-induced cancer cell proliferation and metabolism [ 31 , 39 , 42 ]. However, the most recently discovered 5-HT receptor, 5-HT 7 , is increasingly reported as a new therapeutic target to inhibit cancer proliferation, migration, and invasion [ 28 , 42 , 43 , 44 ]. The current study demonstrated an additional important role of 5-HT 7 in inducing drug resistance and CSCs in pancreatic cancer by elucidating the mechanism regulating 5-HT 7 expression: that is, inhibition of 5-HT 7 by its antagonist or removal of 5-HT via TPH1 inhibition suppressed 5-HT 7 expression in PANC-1 and MIA PaCa-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on pancreatic cancer cell lines and human tumor tissue microarray have shown the role of 5-HT 1B , 5-HT 1D , or 5-HT 2B in 5-HT-induced cancer cell proliferation and metabolism [ 31 , 39 , 42 ]. However, the most recently discovered 5-HT receptor, 5-HT 7 , is increasingly reported as a new therapeutic target to inhibit cancer proliferation, migration, and invasion [ 28 , 42 , 43 , 44 ]. The current study demonstrated an additional important role of 5-HT 7 in inducing drug resistance and CSCs in pancreatic cancer by elucidating the mechanism regulating 5-HT 7 expression: that is, inhibition of 5-HT 7 by its antagonist or removal of 5-HT via TPH1 inhibition suppressed 5-HT 7 expression in PANC-1 and MIA PaCa-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of the dozen or so 5-HT receptors currently recognized, 5-HT receptor 7 (5-HT7) is expressed on GB cells where agonism enhances growth [50][51][52]. This same finding of growth drive stimulation via 5-HT7 is also found in non-small cell lung adenocarcinoma where 5-HT7 agonism drives proliferation, migration, and invasion [53]. Similar growth stimulation by 5-HT7 was seen in neuroendocrine tumors [54], hepatocellular carcinoma [55], and triple negative breast cancer [56,57] 7.…”
Section: 5mentioning
confidence: 85%
“…A functional role for 5-HTRs in human cancers and cancer stem cells is not exclusive to breast cancer, and the genetic depletion of 5-HTRs has deleterious consequences in several tumors of other solid organs and hematological malignancies [ 65 , 66 , 67 , 68 ]. For example, KD of 5-HTR1B and 5-HTR1D inhibits the proliferation and clonogenic capacity of pancreatic tumor cells by inhibiting the activity of transcription factors involved in initiating an EMT [ 68 ].…”
Section: 5-ht and Human Cancersmentioning
confidence: 99%
“…For example, KD of 5-HTR1B and 5-HTR1D inhibits the proliferation and clonogenic capacity of pancreatic tumor cells by inhibiting the activity of transcription factors involved in initiating an EMT [ 68 ]. Similarly, KD of 5-HTR1B dampens the proliferation, migration, and invasive properties of non-small cell lung carcinoma [ 67 ]. In acute myeloid leukemia (AML), 5-HTR1B has a functional role in maintaining therapy-resistant leukemic stem cells [ 66 ].…”
Section: 5-ht and Human Cancersmentioning
confidence: 99%